IMMU-18. TARGETING THE PD1 AND TIGIT CHECKPOINT PATHWAYS FOR ADULT AND PEDIATRIC GLIOMAS. (5th November 2018) - Shoger, Karsen; McCarl, Lauren; Gilbert, Ryan; Villanueva, Clarence; Levy, Nicole; Amankulor, Nduka; Pollack, Ian; Kohanbash, Gary
Abstract: High-grade gliomas (HGGs) are the most common and deadliest of malignant primary brain tumors. Additionally, brain and central nervous system tumors are the leading cause of cancer-related morbidity and mortality in infants and children. Tumors, including HGGs, co-opt immune checkpoint molecules to evade T-cell killing, and targeting these pathways has led to cures in some patients with cancers. Immunotherapy trials, including the use of checkpoint blockade therapies, have been conducted with limited success in brain tumor patients. Our analysis of data from The Cancer Genome Atlas identified that of over 30 assessed checkpoint molecules, only expression of the genes coding for PD1 and TIGIT, within the tumor, were associated with shorter overall survival and progression-free survival times. Furthermore, using published pediatric glioma resources, we found that TIGIT expression is elevated in pediatric HGGs compared with lower-grade pediatric gliomas, and TIGIT expression was inversely associated with overall survival in children with HGGs. These data led us to hypothesize that glioma-associated T-cells express PD-1 and TIGIT, which can be targeted to reduce glioma growth. To test this, we assessed whether mono/combination therapies with anti-PD-1 and anti-TIGIT could improve survival and immune function in a syngeneic orthotopic GL261 glioma mouse model. Although anti-TIGIT therapy alone failed to prolong survival, mice treated with both anti-PD1 and anti-TIGIT demonstrated improved survival compared with mice receiving anti-PD1 alone. Immunologic analysis of tumor-infiltrating cells in our mouse model revealed high expression levels of PVR, the TIGIT ligand, on cells resembling myeloid-derived suppressor cells (MDSCs), within the tumor. Additionally, TIGIT treatment led to the reduction of a subset of T-regulatory cells and cells resembling MDSCs. Overall, our data suggest that anti-TIGIT may reduce immunosuppressive cells at the tumor site and improve the efficacy of anti-PD1 trials in adults and children with HGGs.